The golden compass (His dark materials, 1, 1, 1996)
An over-sized, lavishly illustrated, full-color edition of Philip Pullman's beloved classic. Philip Pullman's The Golden Compass has been changing the world for twenty-five years. We are delighted to offer this new edition of the classic, with more than 100 full-color illustrations from acclaimed illustrator Chris Wormell. A masterwork of storytelling and suspense, The Golden Compass is the story of Lyra and her dæmon familiar and their dangerous journey to the cold, far North, where witch clans and armored bears rule, and where her fearsome uncle is trying to build a bridge to a parallel world... Fans and newcomers alike will be drawn into the story as never before by Wormell's thrilling illustrations.